Incorporating Science and Technology in Higher Education into Strategic Planning for Sustainable Development in Somaliland (Journal of Science, Technology and Innovation Policy, 2021)
Education for Sustainable Development (ESD) is the educational process of achieving human resources with capacities to contribute to the development endeavors of a particular country based on its own priorities. National and international indicators illustrate that there is a big insufficiency in science and technology (S&T) in higher education (HE) in Somaliland/Somalia as compared to other countries in the developing world. This important problem has an effect on the HE institutions’ capacity to deliver S&T programs with the required standards. This problem does not only affect the HEIs but also restricts the young students’ creativity, technical skills and other competencies required in the contemporary world as well as Somaliland development priorities. The problems in S&T with HEIs will block creative and critical thinking, employability, curiosity and positive attitudes of fresh graduates towards contributing to national development. In order to evaluate S&T competencies and capacities of HEIs, this paper uses both input-output S&T indicators. This paper also determines if universities have policies and strategies designated to enhance S&T capacities to ensure improved quality of the S&T programs offered. A questionnaire with 10 items about S&T indicators has been prepared and applied to 6 universities in two different cities (Borama and Hargeisa) of Somaliland. Other literature reviews related to this matter were also reviewed and quoted. According to the result of this research, the main problems with S&T education are of two folds. Firstly, the universities studied do not have S&T strategies and plans, which are supposed to guide and enhance institutional capacities and competencies in S&T provisions in teaching and learning. Secondly, the universities studied also have an insufficient number of S&T lecturers and other facilities/infrastructures and this is the main reason that HEIs’ scientific research output towards sustainable development in Somaliland is totally lacking. As result of this, almost all universities in Somaliland do not offer S&T programs at all levels and those offer these programs do not have sufficient capacity to deliver programs to the expected standards.
Keywords: S&T; Education for Sustainable Development; Policies and Strategies